Transforming Islamic Elementary Education: The Role of Curriculum Management in Quality Improvement - Nurhayati; Lumiati (Al-Qalam Institute, 2025)
This study aims to analyze the implementation of curriculum management and its impact on improving the quality of education in Islamic elementary schools. The research focuses on three key aspects: curriculum planning, implementation, and evaluation within the context of Islamic education institutions that operate under limited resources. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation, and validated using triangulation of sources and techniques. The findings reveal that curriculum planning is conducted collaboratively and systematically, involving school leaders, teachers, and school committees. The implementation stage applies various learning strategies such as project-based learning, differentiated instruction, and the integration of Islamic values across subjects. Evaluation is carried out continuously through academic supervision, reflective meetings, and feedback from parents. The effective implementation of curriculum management positively influences students’ learning outcomes, teacher professionalism, academic culture, and the development of students’ moral and spiritual character. Despite challenges such as limited facilities, funding, and differences in student ability, these are addressed through teacher training, innovative teaching strategies, and active collaboration with stakeholders. Conceptually, this study highlights that well-structured and participatory curriculum management serves as a crucial determinant of educational quality improvement in Islamic educational settings.